Morphotectonics of Mount Rendingan Area Related To the Appearances of Geothermal Surface Manifestations - Gentana, Dewi; Sulaksana, Nana; Sukiyah, Emi; Yuningsih, Euis Tintin (Geological Agency, 2019)
DOI: 10.17014/ijog.6.3.291-309The researched area is situated at Mount Rendingan and its surrounding area, Lampung Province, the southern part of Sumatra Island. It has a big potential of geothermal resource in line with a unique graben like bowl landform and geothermal surface manifestations. This research was carried out using remote sensing and field observation methods. The remote sensing method used topography and Shuttle Radar Topography Mission -Digital Elevation Model (SRTM-DEM) maps to analyze morphotectonic attributes, and the result was validated by morphotectonic data analysis from field observation. The purpose of this research is to evaluate the relation between morphotectonic and the appearances of geothermal surface manifestations. The interpretation of SRTM-DEM and topographic maps are supported by morphotectonic analyses,which indicate that the geothermal surface manifestations in this area are controlled by tectonic activity. It has various levels of lift which are shown by the values of valley height weight ratio (Vf) from 0.16 to 3.31 and the values of mountain front sinuosity (Smf) from 1.05 to 2.09. The morphotectonic characteristics can describe the geological structure activity levels which are reflected in the landform and its rock. The volcanic areas consist of igneous rocks which have small primary permeabilities. However, the development of geological structure can cause fractures in the rock that step in as a medium for passing geothermal fluid from depth to surface. They are found on the fault intersection zone system trending NE-SW and NW-SE, NNE-SSW and NNW-SSE, and WE system directions that indicate the fault system is correlated with the appearances of geothermal manifestations.